"The hare hugs the rabbit. He is white ... Who is white?": Pronominal anaphora in Russian - Gagarina, Natalia Vladimirovna (ZAS Papers in Linguistics, 2007)
This paper investigates the production and comprehension of intrasentential anaphoric pronominal reference in Russian. In particular, it examines the elicited imitation and comprehension of three anaphoric pronouns in subject position – personal 3rd singular masculine, demonstrative and zero – in one hundred and eighty monolingual Russian-speaking children and twenty adults. The three types of pronouns were designed to have an antecedent in the preceding sentence containing a verb and two arguments. These antecedents differ in their syntactical role and animacy. The sentence position, agentivity and topicality remained constant. The sentences with (in)animate subjects and objects constituted the following four 'conditions': two sentences with a subject and an object being either animate or inanimate and two sentences with a subject and an object exhibiting a diverse (in)animacy. Regarding the resolution of the anaphoric pronouns the similarity principle (or feature-concord rule) and its possible violations were tested. This principle suggests that an anaphoric pronoun is most likely resolved to the antecedent with a maximum of similar characteristics or features and it primarily governs the assignment of an antecedent to anaphoric pronouns in subject position in the absence of the violating conditions. Results show the influence of this rule on the anaphora resolution process increasing with age, on the one hand, and the development of the impact of animacy, syntactic role and the type of anaphoric pronouns that violate the feature-concord rule, on the other.